Implementasi Aplikasi Internal Service Order (ISO) Berbasis Web pada Perusahaan Manufaktur Furniture - Simangunsong, Jumadi; Hutagaol, Nindhia; Pasaribu, Faizal Asrul (Politeknik Harapan Bersama, 2024)
Technological advancements and competitive challenges in the industrial sector have driven an increasing need for information systems. The implementation of information systems is believed to significantly enhance a company’s operational effectiveness and efficiency. In the furniture manufacturing industry, production machines are critical assets that require regular maintenance. PT Ebako Nusantara operates more than 200 production machines. Overall, the demand for machine repairs at PT Ebako Nusantara is managed manually, leading to frequent delays and difficulties in tracking repair history. To address these issues, this study was conducted with the aim of utilizing information systems and data analytics, enabling the company to predict machine maintenance and minimize production downtime. The study results show that furniture manufacturing companies that adopt information systems experience a 22% increase in production efficiency and a 50% reduction in production errors. The development process of the ISO application adopts the Agile methodology with six stages: planning, implementation, software testing, documentation, application deployment, and maintenance. The features available in the application include submitting repair requests and tracking machine repairs, which are designed to streamline and expedite the machine repair workflow. This research has facilitated interdepartmental integration in terms of machine repair requests, significantly improving operational efficiency. The use of the ISO application also simplifies the maintenance department’s scheduling of technicians for machine repairs and routine maintenance.